Judje in ideacija o Judih v sodobni Sloveniji - Starman, Hannah (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
In modern times, Jews in Slovenia are marked with their physical non-presence.Despite this fact, it is the starting position in the research project, presented by the author in this contribution, that there exists in contemporary Slovenia a form of so-called "anti-Semitism without Jews". The research will encompass the ideation on Jews, Jewry, Israel and other formative themes as popularised in the media, and contrast them against the empirical evidence of testimonies among: Holocaust survivors and their offspring; witnesses and bystanders of Holocaust in Slovenia; and persons who cite Jews as ancestors in the context of family genealogies. The research pursues two explicit goals: documenting the testimonies of Holocaust survivors, and circumferential evidence, in Slovenia; and the present-day attitude towards Jews and Jewry as a component factor in the identity professions in the framework of ethnic differentiations in present-day Slovenia.
Keywords: Slovenia; Slovenija; Židje; antisemitizem